2019
DOI: 10.48550/arxiv.1907.08210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modular Bosonic Subsystem Codes

Giacomo Pantaleoni,
Ben Q. Baragiola,
Nicolas C. Menicucci

Abstract: We introduce a formalism for encoding a qubit into a bosonic mode as a discrete subsystem. Using a modular decomposition of the position operator, we divide the bosonic mode into two subsystems: a logical qubit and a gauge mode. This formalism enables the analysis of continuousvariable quantum information using standard qubit-based quantum information tools. We apply the formalism to approximate Gottesman-Kitaev-Preskill (GKP) states and show that the logical qubit experiences decoherence due to entanglement w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…VII. The first is that for large average excitation number in the code, the performance (as measured 22 Recently it was shown that GKP codes can be decomposed into two subsystems-a logical qubit and gauge mode-according to their discrete translation symmetry [92], and a similar decomposition for rotation codes based on discrete rotation symmetry is likely. Note that the translation symmetry of any GKP code also implies two-fold rotation symmetry (see Appendix C).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…VII. The first is that for large average excitation number in the code, the performance (as measured 22 Recently it was shown that GKP codes can be decomposed into two subsystems-a logical qubit and gauge mode-according to their discrete translation symmetry [92], and a similar decomposition for rotation codes based on discrete rotation symmetry is likely. Note that the translation symmetry of any GKP code also implies two-fold rotation symmetry (see Appendix C).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In order to analyze the relation among the three approximations, we derive the position and momentum representations, q q|j and p p|j , of the approximate code states. Note that the position and momentum representations of Approximation 1 have already appeared in the past literature [7,9,23,35,37,38,40,42,44,45], but we rewrite them for the completeness. For that, we first define the following functions.…”
Section: The Equivalence Of the Approximations A Position And Momentu...mentioning
confidence: 99%